Models of Affective Illness: Chronic Mild Stress in the Rat. Issue 3 (9th March 2023) - Papp, Mariusz; Willner, Paul
Abstract: This article describes a chronic mild stress (CMS) model for predicting antidepressant response and investigating mechanisms of antidepressant action in rats. Following exposure to a variety of mild stressors for several weeks, the rats' behavior is modified in several ways that parallel symptoms of depression. Among these is a substantial reduction in consumption of a 1% sucrose solution, which models the cardinal symptom of major depression, anhedonia. Our standard procedure employs a battery of behavioral tests, comprising weekly assessment of sucrose intake and, at the end of treatment, the elevated plus‐maze and novel object recognition tests to assess the anxiogenic and dyscognitive effects of CMS. Chronic administration of antidepressant drugs reverses the decreased sucrose intake and other behavioral changes in these subjects. Also effective are second‐generation antipsychotics. The CMS model can be employed in discovery programs to identify anti‐anhedonic drugs (e.g., antidepressants and antipsychotics) that act more quickly than existing agents. While most antidepressants require 3 to 5 weeks to normalize behavior, some treatments provide a faster onset of action. For example, the CMS‐induced deficits can be reversed by acute or sub‐chronic application of treatments that act rapidly in depressed patients, such as deep brain stimulation (DBS), ketamine, and scopolamine, as well as several compounds that have yet to be tested in humans but have fast‐onset antidepressant‐like effects in animals, such as the 5‐HT‐1A biased agonists NLX‐101 and GLYX‐13. Application of the CMS model in Wistar‐Kyoto (WKY) rats causes similar behavioral changes to those seen in Wistars, but these are not reversed by antidepressant treatment. However, WKY rats respond to DBS and ketamine, which are effective in patients who are antidepressant non‐responders, establishing CMS in WKY rats as a model of treatment‐resistant depression. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol : Induction of chronic mild stress in rats as a model of depression and treatment‐resistant depression